2006
DOI: 10.1007/s11157-006-9101-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypometabolic induced state: a potential tool in biomedicine and space exploration

Abstract: This paper will first review the issue of hypometabolism in mammals with a focus on the strategies these animals evolved to cope with life challenge in hostile environments (e.g., cold weather and/or shortage of food). The different types of natural hypometabolism (hibernation, torpor, winter sleep) will be briefly described as well as major adaptations in body temperature, and energy and cell metabolism. In the second part of this review the issue of inducing a hypometabolic state in mammals will be afforded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…Because of their morphological appearance as well as to the presence of snRNPs and SMN protein (Malatesta et al, 2004), NADs strongly remind the interchromatin granule-associated zones (IGAZ), that is, nuclear domains occur close to IG clusters (Visa et al, 1993); however, IGAZs contain coilin (Puvion-Dutilleul et al, 1995) and cleavage factors (Cardinale et al, 2007), which are absent in NADs. Therefore, the NADs occurring in hazel dormice seem to represent nuclear structures typical of the hibernating state, like several nuclear bodies found in different tissues, which, similarly to NADs, form during lethargy and quickly disappear upon arousal [reviewed in Malatesta et al (2007)]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their morphological appearance as well as to the presence of snRNPs and SMN protein (Malatesta et al, 2004), NADs strongly remind the interchromatin granule-associated zones (IGAZ), that is, nuclear domains occur close to IG clusters (Visa et al, 1993); however, IGAZs contain coilin (Puvion-Dutilleul et al, 1995) and cleavage factors (Cardinale et al, 2007), which are absent in NADs. Therefore, the NADs occurring in hazel dormice seem to represent nuclear structures typical of the hibernating state, like several nuclear bodies found in different tissues, which, similarly to NADs, form during lethargy and quickly disappear upon arousal [reviewed in Malatesta et al (2007)]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on several tissues of hibernating rodents revealed that the cell nucleus undergoes important structural reorganization during the hypometabolic period: RNA transcription and maturation factors redistribute among the nuclear constituents; various nuclear bodies, which contain splicing factors, do form during the lethargic period and disappear upon arousal; the nucleolus undergoes structural and molecular modifications (Malatesta et al, 2007(Malatesta et al, , 2008. In particular, during hibernation, the nucleolus is characterized by irregular shapes due to many nucleoplasmic invaginations, which sometimes contain weakly contrasted areas of unknown nature.…”
Section: Introductionmentioning
confidence: 99%
“…Natural hypothermia occurs in the majority of mammalian families, suggesting that torpor may be possible for many, if not all, mammals (Heldmaier et al 2004). Torpor physiology has recently attracted increased attention for its potential therapeutic applications (Carey et al 2003), which include neuroprotection in cardiac-arrest patients, preservation of organs for transplantation, and the treatment of neurodegenerative diseases like Alzheimer's (Malatesta et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These animals are, in fact, able to drastically lower their body temperature and to reduce all metabolic and physiological activities, thus facilitating survival under adverse environmental conditions; however, as soon as the situation reverts to favorable conditions, they leave the depressed metabolic state restoring the euthermic functions in a short time (Lyman et al, 1982). Previous studies on several tissues of hibernating rodents revealed that the cell nucleus undergoes important structural reorganization during the hypometabolic period; various nuclear bodies containing transcription and splicing factors do form during the lethargic period and disappear upon arousal, and the nucleolus undergoes structural and molecular modifications as well (reviews in Malatesta et al, 2005Malatesta et al, , 2007. However, the nuclear structural constituents involved in pre-mRNA transcription and processing do not show evident morphological modifications during hibernation, despite the severe inhibition of the transcriptional activity (van Breukelen and Martin, 2002).…”
Section: Introductionmentioning
confidence: 99%